Degradación de microcuencas de gran valor geobotánico en la zona costera mediterránea de Chile. Antecedentes para restauración ecológica - Quintanilla Pérez, Victor; Morales Constanzo, Mauricio (Geographicalia, 2014)
A study is made of the plant communities that exist in two coastal microbasins, from a biogeographical stand point: Quebrada San Jerónimo and Quebrada Córdova, considering their spatial distribution and the relations that exist in the different natural environments of these wet microreliefs that drop from coastal slopes of the central Chile’s mediterranean zone. Basically, the existence of wet microclimates with constant fog favors the development of species from wet forests, and it is stressed that in the Córdova microbasin there are species belonging to plant formations of the south of Chile with three endemic plants, and there is also a relict forest of a southern tree, Aextoxicon punctatum. Nevertheless, these microbasins are affected by fire, erosion, and anthropic disturbance, so there is an urgent need to apply recovery and ecological restoration measures. The degradation is a constant process.
Keywords: Sclerophyllous; fire; erosion; degradation; relict; restoration.